FORDANSKNINGEN AF KULTURLANDSKABET: Midtvejsrapport fra et registreringsprojekt - Adriansen, Inge (Tidsskriftet Antropologi, 2000)
In the 19th and 20th centuries several thousand national monuments and memorials have been erected all over Denmark. In close co-operation between the National Museum and the author questionnaires have been sent to all municipalities in order to record the national memorials in each municipality all over the country. The response rate is very high and all answers have been registered in a database. The data processing reveals that the most widely distributed memorial tells about Danish identity and a type of feeling of community based on history. Furthermore, the historical conflicts between Denmark and Germany have caused an amazing number of memorials. Opposition and resistance to the Germans have strengthened the national identity of the Danes and caused a "nationalization of the scenery".